1978
DOI: 10.1159/000275385
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and Vertical Optokinetic Nystagmus in Man

Abstract: Horizontal and vertical optokinetic nystagmus (OKN) was studied in 20 healthy adults. Although the horizontal OKN showed no directional difference, a statistically significant difference was found between horizontal and vertical OKN. Upward optokinetic pursuit was better on average than downward pursuit, but more variable. The inferiority of vertical OKN seems to indicate a suppression of optokinetic pursuit due to a different direction of the rotational axis from that of gravity. Regarding the vertical OKN fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 7 publications
1
20
1
Order By: Relevance
“…They have reported an OKN gain, elicited by a 30°/sec drum speed, between 0.9 (9) and nearly 1.0 (6,7,23), or a gain, elicited by 60°/sec, which varied between 0.7 (7, 11) and nearly 1.0 (3,14,16,23). Two reasons may explain the quite lower values found in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…They have reported an OKN gain, elicited by a 30°/sec drum speed, between 0.9 (9) and nearly 1.0 (6,7,23), or a gain, elicited by 60°/sec, which varied between 0.7 (7, 11) and nearly 1.0 (3,14,16,23). Two reasons may explain the quite lower values found in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Upward stimulus motion evokes more robust OKN than downward motion. [19][20][21][22][23][24][25][26][27] An upward bias of vertical OKN in humans has been reported consistently in studies using magnetic search coil eye movement recordings. Conflicting results have been reported when EOG or infrared recording methods are used, which are subject to eyelid interference artifact during vertical eye motion.…”
Section: Vertical Okn Asymmetrymentioning
confidence: 99%
“…Upward (UW) stimulus motion evokes more robust OKN than downward (DW) motion. [19][20][21][22][23][24][25][26][27] In children and adults with strabismus and/or amblyopia, the asymmetry favoring upward OKN may be more pronounced. 25,28,29 Behavioral studies have shown that the postnatal development of binocular sensory and motor functions in infant NHPs parallels closely that of infant humans, but on a compressed time scale (i.e., 1 week of monkey development is equivalent to 1 month of human).…”
mentioning
confidence: 99%
“…In man, the asymmetry of the vertical OKN in an upright position is not significant and can be detected only occasionally [Ohm, 1922;Krieger and Bender, 1956;Stiefel and Smith, 1962;Collins et al, 1970;Rosberg et al 1972;Takahashi et al, 1978;Koempf et al, 1979;King and Leigh, 1982;Baloh et al, 1983]. It has been known that, in general, the vertical OKN cannot be provoked as easily as the horizontal one Collins et al, 1970;Baloh et al, 1983].…”
Section: Vertical Optokinetic Nystagmusmentioning
confidence: 99%